Rapid Two-Temperature Formalin Fixation - Chafin, David (Public Library of Science, 2013)
Formalin fixation is a mainstay of modern histopathologic analysis, yet the practice is poorly standardized and a significant potential source of preanalytical errors. Concerns of workflow and turnaround time drive interest in developing shorter fixation protocols, but rapid protocols can lead to poor histomorphology or inadequate downstream assay results. Additionally, assays such as immunohistochemistry for phosphorylated epitopes have historically been challenging in the context of formalin-fixed tissue, indicating that there may be room for improvement in this process that is fundamental to the practice of anatomic pathology. With these issues in mind, we studied basic formalin biochemistry to develop a novel formalin fixation protocol that involves a pre-incubation in subambient temperature formalin prior to a brief exposure to heated formalin. This new protocol is more rapid than standard protocols yet preserves histomorphology and yields tissue that is compatible with an expanded set of downstream clinical and research assays, including immunohistochemistry for phosphorylated epitopes.